A Novel Fluorinated Schiff Base: Synthesis, Spectroscopic Characterization, and Quantum Chemical Study - Sapkota, Kamal Raj; Anand, Vaishali; Faizi, Md. Serajul Haque; Roy, Ansu Kumar; Gupta, Rahul Kumar; Haque, Navedul (Kaumodaki: Journal of Multidisciplinary Studies, 2026)
In this study, we report the design, synthesis, and comprehensive characterization of (E)-N-((1H-pyrrolo[2,3-b]pyridin-4yl) methylene)-2-fluoro-5- (4H-1,2,4-triazol-4-yl)aniline (PTA), a novel Schiff base integrating three bioactive motifs— pyrrolo[2,3-b]pyridine, 1,2,4-triazole, and fluorinated aniline—linked through a conjugated azomethine group. PTA was synthesized via condensation of 2-fluoro-5-(4H-1,2,4-triazol-4- yl)aniline with 1H-pyrrolo[2,3-b]pyridine-4-carbaldehyde under mild reflux conditions, affording a yellow solid in 81% yield. Its molecular structure was confirmed using Fourier-transform infrared spectroscopy (FT-IR), nuclear magnetic resonance spectroscopy (NMR), ultraviolet–visible spectroscopy (UV–Vis), and mass spectrometry. Density Functional Theory (DFT) analyses, including frontier molecular orbital (FMO) and molecular electrostatic potential (MEP) studies, revealed a HOMO–LUMO gap of 3.562 eV, indicating moderate kinetic stability, and identified regions favorable for electrophilic and nucleophilic interactions. Molecular docking with the sulfonylurea receptor SUR1 (PDB ID: 6PZI) demonstrated stable binding through hydrogen bonding, π–π stacking, and van der Waals interactions, highlighting PTA’s potential as an antidiabetic lead. The combined experimental and theoretical findings suggest that PTA’s conjugated framework and electronic properties may be exploited in medicinal chemistry and optoelectronic applications.